Loop Array Antenna in a Borehole for Directivity to a Horizontally Polarized Wave - Ebihara, Satoshi; Matsumoto, Masayuki (IEEE transactions on geoscience and remote sensing, 2022)
We propose a directive antenna for borehole radar using a horizontally polarized wave in a vertical borehole. This antenna is an array of several horizontal loop antennas, arranged vertically. When a plane wave is incident on the antenna, the differences in arrival times at the array elements enable us to estimate the direction of arrival (DOA). We present a simple model representing the arrival time difference and propose an algorithm for DOA estimation. Furthermore, we synthesized the array signal by analyzing the electromagnetic field using the method of moments (MoM) and applied the proposed algorithm to the signal. We found that mutual coupling between antenna elements affects the DOA estimation and that a space of about 3 cm between antenna elements prevents mutual coupling. Using the MoM analysis, we simulated a cross-hole measurement to demonstrate the antenna's ability. We carried out field experiments in wet soil to examine the antenna's ability. The proposed loop array antenna in a water-filled borehole received a direct wave from a source in another borehole. After applying the proposed algorithm to the measured data, we found that we could estimate the DOAs to the source with an error of less than 15° in the azimuth angle and 10° in the elevation angle.